Analisis Juridis UU Nomor 7 Tahun 2017 Periode Pemilu Tahun 2024 Terkait Pemasangan Alat Peraga Kampanye yang Melanggar Ketentuan di Sulawesi Utara - Douglas Lucky Hanny Mandagi; F.X. Wartoyo; Agustin Widjiastuti (CV Rewang Rencang, 2024)
The installation of Campaign Props (APK) is part of the democratic process regulated in Article 298 of Law Number 7 Year 2017 on General Elections. However, the practice of installing APKs often has a negative impact on the environment, such as visual pollution and plastic waste. This research analyses the implementation of APK installation rules in the 2024 General Election in North Sulawesi with a normative legal approach. The results show that there are still many violations, such as installation in public facilities and the use of environmentally unfriendly materials. Stricter supervision, strict law enforcement, and socialisation are needed to increase awareness of sustainable APK installation rules.